ChemInform Abstract: Double C—H Functionalization to Construct Polycyclic Heteroarenes Catalyzed by an Ionic Salt of a Pd Complex with an N‐Heterocyclic Carbene Ligand. Issue 46 (November 2015) - Ghosh, Sanjay Kumar; Kuo, Bing‐Chiuan; Chen, Hsiang‐Yu; Li, Jia‐Ying; Liu, Shuang‐De; Lee, Hon Man
Abstract The new ionic salt catalyzes the double C—H activation of nitrogen‐ and sulfur‐containing heterocyclic substrates in oxidative coupling reactions with alkynes.